Bioprospecção do óleo essencial das folhas de Myrcia guianensis (Aubl.) DC. da Amazônia Legal com propriedade antibacteriana: Contribuição para o desenvolvimento de novos medicamentos. - SILVA , Marcos Vinícius Soares (2020)
Myrcia guianensis (Aubl.) DC, a species belonging to the Myrtaceae family, has a geographic distribution throughout Brazil, being an endemic plant in tropical areas and with potential for the development of products of interest. This work aimed to carry out a bioprospecting study of the species Mycia guianensis determining the chemical composition from its leaves essential oil and, still, evaluating its potential for antibacterial activity and toxicity. The collection was carried out in the Chapada das Mesas National Park, Legal Amazon, in March 2018 and the extraction of essential oil occurred by hydrodistillation process. The chemical components identification was performed by gas chromatography coupled with mass spectrometry. The in silico analysis of the potential antimicrobial activity and toxicity was carried out with the major components of the essential oil performing software such as PASS, Osiris, PROTOX and SwissADME. The in vitro evaluation of the essential oil occurred against Staphylococcus aureus (ATCC 6538), Pseudomonas aeruginosa (ATCC 27853), Escherichia coli (ATCC 042), Klebsiella pneumoniae (clinical isolate), and methicillin resistant Staphylococcus aureus (MRSA)(clinical isolate strain 01 and 02) to determine the minimum inhibitory concentration (MIC), antibiofilm activity of essential oil, viability and metabolic activity bacterial. In order to assess toxicity, an in vivo infection model induced by Staphylococcus aureus in Tenebrio molitor larvae was performed. Beyond that, there was a performance evaluation of bacterial load in the hemolymph from Tenebrio molitorlarvae after 24 hours comparing the essential oil and ciprofloxacin. The Myrcia guianensis leaves essential oil showed a good yield, 1.34%, with the major components identified: (E-)-caryophyllene (35.22%), terpinolene (13.76%) and β-bisabolene (6.13%). The evaluation through the software showed good antimicrobial potential and low toxicity of the major compounds. In the in vitro evaluation, the results were promising against tested Gram-positive strains, especially Staphylococcus aureus (ATCC 6538) and clinical isolates MRSA, while showing little or no effect against tested Gram-negative strains, except for the potential antibiofilm against Escherichia coli (ATCC 042). Regarding toxicity in both in silico and in vivo analysis, no toxic effect was observed, in addition to confirming the antibacterial potential with the drastic reduction in bacterial load in the evaluation of the hemolymph of the Tenebrio molitor larvae. Therefore, the essential oil presents promising results against Staphylococcus aureus, representing a good alternative for potential product of pharmaceutical interest.